Biomechanical Variances in the Development of Forward Head Posture - Yasemin Deniz; Esra Pehlivan; Eda Cicek (Korean Research Society of Physical Therapy, 2024)
Forward Head Posture (FHP) involves the anterior positioning of the head relative to the shoul-ders, often associated with muscular imbalances. It is known that individuals with FHP expe-rience shortening of craniocervical extensors and cervical flexors. However, contrary to the understanding of flexion in the craniocervical extension subaxial region, a study has reported flexion in the craniovertebral spinal vertebrae among individuals with FHP. The aim of this study was to examine the consistency of biomechanical study results conducted for FHP. The relevant studies were investigated in PubMed and Google Scholar databases using the key-words "forward head posture OR cervical sagittal alignment OR cervical spine AND biome-chanics OR kinetic analysis OR kinematic analysis." During the research selection process, only nine studies relevant to the purpose of our study were identified. Out of these nine studies, four conducted kinematic analysis related to FHP formation, while six conducted kinetic analy-sis. During the comparison of these studies, five inconsistencies were identified. Biomechanical studies on FHP reveal conflicting findings, suggesting potential variability in the biomechanics of FHP formation across individuals. However, drawing definitive conclusions requires further exploration through additional biomechanical investigations on FHP in the future.